The best school year ever - Robinson, Barbara, 1927- (New York : HarperCollins, 1994)
The six horrible Herdmans, the worst kids in the history of the world, cause mayhem throughout the school year.
Sequel to: The best Christmas pageant ever.
Elem. School Library Collection.
School Library Journal.
Wilson's Junior High School.
5.4.
5.4
Keywords: Humorous stories; Schools -- Fiction; Humorous fiction; School stories